Influence of duration of dietary vitamin E supplementation on fresh and cured pork color stability - J F Stika; John A Unruh; Donald H Kropf; Melvin C Hunt; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1998)
Supplementing finishing pigs genetically predisposed to lipid deposition with atocopheryl acetate above 12 IU/lb of feed for as long as 70 d did not improve color stability of fresh and cured pork. Tissue a-tocopherol levels were similar across dietary treatments and higher than predicted. Muscle accumulation of a-tocopherol may be related to the rate and extent of lipid deposition in muscle. Also, chill temperature and carcass chill rate variability, under spray chill conditions, did not influence fresh pork color stability when carcasses with excessive amounts of external fat were utilized.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Pork; Viatmin E; Chill rate